The Geometric Music of “Three Hierarchs” Church from Iaşi - Cristian Ungureanu (Anastasis: Research in Medieval Culture and Art, 2015)
In order to emphasize the links between science and art, we analyse the “Three Hierarchs” Monastery church, Moldavian architecture masterpiece of the 17th century, build by the Voivode Vasile Lupu. The artistic project which reunited in a perfect harmony `quotes`of the geometrical decorations belonging both to the Balcans Christian and the Islamic culture, which were gathered harmoniously in a common body, stable and unitary.The study of the consecutive structures of the “flowers of the numbers” that build up the visual engines of the 61 rosettes carved in stone, that highlight the sculpted decorations of Trei Ierarhi church, has the aim to associated the geometric models with musical/vibrational structures derived from these.